Analisis Perbandingan Sistem Manajemen Bandwidth Berbasis Class-Based Queue Dan Hierarchical Token Bucket Untuk Jaringan Komputer - Bagas Prawira Adji Wisesa; Aswin Suharsono; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Voice over Internet Protocol (VoIP) service, which is delay-sensitive and File Transfer Protocol (FTP) services with delay-tolerant. With bandwidth management, bandwidth can be set according to the needs of the application. In addition, bandwidth management can also lend out bandwidth has been allocated in accordance with priorities in order to optimize the use of bandwidth. Class-Based Queue (CBQ) method and Hierarchical Token Bucket (HTB) method is bandwidth management mechanism based on the priority class that can be run in the ubuntu operating system. This study applies the Class-Based Queue (CBQ) method and Hierarchical Token Bucket (HTB) method on different types of traffic such as VoIP and FTP. Parameters of Quality of Service (QoS), which include delay, jitter and throughput. From the results of testing, Hierarchical Token Bucket (HTB) method more appropriately applied to VoIP traffic and also FTP. QoS parameters, in accordance with the value obtained when using the VoIP Hierarchical Token Bucket (HTB) method without priority i.e. delay at 14.35 ms, jitter and throughput ms 0.25 and 0.15 MBit/s. While at FTP i.e. delay 31.93 ms and 0.37 MBit/s throughput.